Propietarios y empresarios españoles en La Laguna (1870-1910) - Cerutti, Mario (El Colegio de México, A.C., 1999)
Although limited in size, Spanish immigration was undeniably important for the formation of Mexico's capitalist society  and business community. Because of the activities they carried  out, their high participation in the business sectors that grew after the mid-nineteenth century, and their geographic distribution, Spaniards should be reconsidered in economic-business history. The Spanish immigrants who established themselves in Northern Mexico carme mostly from Northern Spain. Immigrants from Austrias, Santander, and the Basque Provinces helped from many commercial, mining, agricultural, industrial, and service enterprises. Spaniards were particularly active at the Comarca Lagunera, a semi-desertic setting which, after 1870, became, one of Mexico's major end-of-the-century agricultura emporia. After reviewing this spectacular development of agriculture -as well as of  agroindustry, manufacturing, banking, and  services-, this work centers on three cases: the Basque Rafael Arocena y Arbide, the house of Hernández Hermanos Sucesores (Basque-Santander), and Santiago Lavín (from Santander).